Ultrathin silicon micropackaging for RF MEMS devices - Kim, YK; Park, YK; Kim, JK; Kim, SW; Ju, BK (ELECTROCHEMICAL SOC INC, 2006)
In this paper we report a technology for lightweight, small radio-frequency (rf) microelectromechanical system packaging with a short electrical path length. We used an ultrathin silicon substrate as the packaging substrate. Via holes for vertical feed-through were fabricated on the thin silicon wafer. Then, bottom-up gold electroplating was applied to fill via holes. For hermetic sealing, gold-gold direct metal bonding was used in the sealing line. The packaged rf device has a reflection loss below -22 dB and an insertion loss of -0.05 to -0.08 dB. Therefore, with the ultrathin silicon wafer, a lightweight, small device package can be constructed.